Pengaruh Kapitalisasi Pasar, Kebijakan Deviden Dan Kebijakan Hutang Terhadap Tingkat Pengembalian Saham Yang Dimoderasi Profitabilitas - Aulia Pramesti; Nera Marinda Machdar (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
The more advanced a country’s economy is, the greater the role of the capital market will be. The important role of the capital market in the economy is firstly as a means of business funding. Funds obtained from the capital market can be used for business development, expansion, additional working capital and so on (Retnaningrum & Haryanto, 2020). The capital market provides investors with the opportunity to invest their funds in various financial instruments, such as shares and bonds. If the investment produces profits, investors will feel better investing in the long term.